Ranganathan's Theory of Fact Analysis and Knowledge Representation - Gopinath, M.A. (DESIDOC Journal of Library & Information Technology, 2002)
Presents the basis of Ranganathan’s theory of Facet Analysis and identifies its application to the analysis of knowledge. Discusses its value in knowledge representation in different contexts. http://dx.doi.org/10.14429/dbit.12.5.3064